2019
DOI: 10.1002/ajh.25388
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of acquired aplastic anemia in Tanzania

Abstract: Acquired aplastic anemia (AA) is a rare disease, with an estimated frequency-in Europe and in North America-of about 2 cases per million population per year. 1 There are reports of AA from North Africa, 2 West Africa, 3 East Africa, 4 and Southern Africa, 5 but no data on the frequency of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…In an adult cohort from Tanzania, a 42.0% prevalence of PNH clones in AA patients was found. 31 Interestingly, this study also showed an overall higher AA prevalence of six cases per million per year, compared to two per million per year in Europe and North America. A study among a paediatric cohort from Egypt showed the presence of a PNH clone in 36.0% of patients using the CD59 immunohistochemical staining on bone marrow trephine biopsies.…”
Section: Discussionsupporting
confidence: 49%
“…In an adult cohort from Tanzania, a 42.0% prevalence of PNH clones in AA patients was found. 31 Interestingly, this study also showed an overall higher AA prevalence of six cases per million per year, compared to two per million per year in Europe and North America. A study among a paediatric cohort from Egypt showed the presence of a PNH clone in 36.0% of patients using the CD59 immunohistochemical staining on bone marrow trephine biopsies.…”
Section: Discussionsupporting
confidence: 49%
“…Since PNH is ultra-rare, it is not surprising that there have been very few cases reported from Africa (Manuel, 1969;Oni et al, 1970;Rizk et al, 2002;Lumori and Muyanja, 2019); in Tanzania we have so far diagnosed four patients (Ally et al, 2019). At the moment, as far as we know, ECU is not available in Africa, or in most Asian countries (including India and China), or in most countries in Latin America, and even in some EU countries.…”
Section: Paroxysmal Nocturnal Haemoglobinuriamentioning
confidence: 96%
“…Aplastic anaemia (AA) is another condition that can be treated with HSCT. An observational study conducted at a teaching hospital in Dar es Salaam, reported a high incidence of (AA), with a mortality rate of 48%; 15 85% of patients diagnosed had severe or very severe AA, with 80% being diagnosed under the age of 40. The third haematological condition that is a common indication for HSCT is acute leukaemia.…”
Section: Unmet Needs Of Stem Cell Transplantation In Low To Middle Inmentioning
confidence: 99%